Pachyonychia congenita: A case report - Silpa Ramachandran; Suman Jhansi Lakshmi; Elangovan Somasundaram; Senthil Kumar Balasubramanian (Wolters Kluwer Medknow Publications, 2019)
Pachyonychia congenita (PC) is a rare autosomal dominant disorder of keratinization. It is usually present at birth or develops within 1 year of birth. It is classified into four types, but type-1 (Jadassohn-Lewandowsky type) and type-2 (Jackson-Lawler type) are the most common. PC is characterized by dystrophic, thickened nails, and painful palmo-plantar keratoderma. The nails are dramatically affected in most patients, but oral lesions are seen in patients affected by the Jadassohn-Lewandowsky type. In literature, fewer than 500 cases have been reported about PC. We report a case of PC in an 18-year-old male patient who presented with subungual hyperkeratosis, palmar-plantar keratosis, and leukokeratosis.